Effects of cell-mediated osteoprotegerin gene transfer and mesenchymal stem cell applications on orthodontically induced root resorption of rat teeth - KURT, GÖKMEN; Amuk, Nisa Gul; Kurt, GÖKMEN; Baran, Yusuf; Seyrantepe, Volkan; Yandim, Melis Kartal; Adan, Aysun; Demir, Secil Akyildiz; Kiraz, Yagmur; Sonmez, Mehmet Fatih (My University, 2017)
Aim: The aim of this study is to evaluate and compare therapeutic effects of mesenchymal stem cell (MSCs) and osteoprotegerin (OPG) gene transfer applications on inhibition and/or repair of orthodontically induced inflammatory root resorption (OIIRR).